Rumen microbial changes in calves fed on alpha amylase diet - Kmet, V; Jonecová, Z; Tirco, M; Koniarová, I; Kirchnerová, K; Ceresnáková, Z (Archiv fur Tierernahrung, 1988)
Fifty-six calves in the period of a milk nutrition, randomly assigned to two groups (control and alpha amylase fed) were used to monitor the changes in the rumen microbial populations and total volatile fatty acids (VFA) concentrations associated with feeding Amylosubtilin G10X (0.6 g.day-1). Statistically significant increase was observed for amylolytic counts in experimental calves on 20th or 30th days. The counts of rumen cellulolytic bacteria and selenomonas tended to have increase in the value, but were not significantly different from those in the control valves. The results show that alpha amylase fed calves has a relative higher rumen microbial population.
Keywords: skot; Animals; Cattle; dieta; bachor; alfa-amylasy; Bacteria; Diet; alpha-Amylases; zvířata; Rumen